Проблеми глобалізації та форми їх прояву - Яковенко, Р. В.; Yakovenko, R.; Бірзул, Н. Д.; Birzul, N. (Кіровоград : видавець Лисенко В. Ф., 2015)
Стаття розкриває суперечності глобального поступу світу, форми глобалізації та визначальні глобальні проблеми. The article reveals the contradictions of the global evolution of the world, the forms of globalization and the determinative global problems.
The problems of globalization and the form of their manifestation
Keywords: глобалізація; міжнародна торгівля; екосистема; транснаціональні корпорації; globalization; international trade; ecosystem; transnational corporations